Pandora's poison : chlorine, health, and a new environmental strategy - Thornton, Joe. (Cambridge, Mass. : MIT Press, 2000)
"Pandora's Poison presents a solution to one of the most insidious environmental problems of our time: the global build up to toxic chemicals. In a through and accessible analysis, biologist Joe Thornton shows how global organochlorine pollution is already contributing to infertility, immune suppression, cancer, and developmental disorders in humans and wildlife." "Articulating principles for a new environmental strategy, Thornton shows that the only practical solution is to take global action on broad classes of hazardous chemicals and the processes that produce them, starting with organochlorines. He lays out a democratically controlled program to replace the production and use of chlorine gas and its derivatives with safer, effective, and economically feasible alternatives, which are already available for the majority of chlorine uses. Pandora's Poison promises to revolutionize the debate over pollution, health, and the role of science in public policy."--Jacket.
Introduction: The Argument -- I. The Problem: A Global Health Hazard -- 1. Organochlorines Around the World -- 2. First-Class Poisons: The Toxicology of Organochlorines -- 3. The Damage Done: Health Impacts in People and Wildlife -- 4. Organochlorines and Cancer -- II. The Cause: Industrial Chlorine Chemistry -- 5. Chlorine in Nature and Industry -- 6. The Chlorine Business -- 7. Chemistry out of Control -- 8. Major Sources of Organochlorine Pollution -- III. The Solution: A Chlorine Sunset -- 9. An Ecological Policy on Chlorine Chemistry -- 10. Beyond Chlorine: The Alternatives -- 11. Good Science, Good Politics.
Includes bibliographical references (pages 513-580) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Organochlorine compounds -- Toxicology; Organochlorine compounds -- Environmental aspects; Environmental policy; Organic compounds; Poisons; Chlorine -- toxicity; Organic Chemicals; Environmental Pollution -- prevention & control; Insecticides, Organochlorine; Poisons; Composés organochlorés -- Toxicologie; Composés organochlorés -- Aspect de l'environnement.; Environnement -- Politique gouvernementale; Composés organiques; Poisons; environmental policy; organic compounds; poison; MEDICAL -- Toxicology; Poisons; Organic compounds; Environmental policy; Organochlorine compounds -- Environmental aspects; Organochlorine compounds -- Toxicology; Toxicologie; Chloorverbindingen; Milieutoxicologie; Gezondheidseffecten; Milieueffecten; Toxicology & Public Health; Public Health; Health & Biological Sciences